Design and development of a universal accelerometer mounting device for structural vibration measurements - Kwong, Kok Yi (2014)
Vibrations are mechanical oscillations produced by movements of a body about its equilibrium position. Vibrations can be a source of problems to structures and induce discomfort in human beings which underscores the need for structural vibration measurements. Proper mounting of accelerometers on test surfaces is crucial in obtaining accurate results. Despite this, there is an absence of a universal accelerometer mounting device in the market. The objective of this project is to design and develop a universal accelerometer mounting device that could be securely attached onto flat surfaces of large structures such as buildings for vibration measurements. The mounting device should not adversely affect the test surfaces and quality of data captured by the accelerometer. Using the information gathered from surveys and interviews conducted with engineers from Vipac Engineers & Scientist Pte Ltd, various designs of the mounting device are developed. After which, a prototype of the selected design is fabricated and tested. Data collected are analyzed to determine the performance of the prototype before implementing modifications to achieve optimal results. The final design was found to have met with the objectives of the project. In addition, the useful frequency range of the universal accelerometer mounting device is determined to be 0 Hz to 48 Hz with a deviation of +5% to -15 %. The natural frequency of the device is found to fall in the frequency range of 65 Hz to 75 Hz. Implementation of the device increases efficiency of vibration measurements by providing greater convenience to the operators. Recommendations for future work include modifying the design to accommodate curved test surfaces.